Use of Contrast-Enhanced Ultrasound of the Testes after Non-Surgical Sterilization of Male Dogs with CaCl2 in Alcohol - Vincenzo Cicirelli; Francesco Macrì; Simona Di Pietro; Raffaella Leoci; Giovanni Michele Lacalandra; Giulio Guido Aiudi (Animals, 2022)
Sterilization by intratesticular injection of chemical agents is a non-surgical alternative to neutering male companion animals. We used contrast-enhanced ultrasound (CEUS) to monitor vascular alterations to testes immediately after the intratesticular injection of CaCL2 in alcohol. We evaluated the CEUS features of normal and damaged testes in 20 dogs after the intratesticular injection of CaCl2. The CEUS evaluation was performed at the site of the chemical agent inoculation. In treated testes, qualitative CEUS showed a lower intensity enhancement of the parenchyma than pre-treatment normal testes with a predominantly anechoic pattern and only a few hyperechoic vascular focal spots. Quantitative CEUS showed significantly lower values of time-intensity curve (TIC) parameters, including signal intensity (Peak: 4.72 ± 2.1), regional blood volume (RBV: 134.3 ± 63.7), and regional blood flow (RBF: 4.36 ± 2.18) than normal testes (p < 0.001). Sonographic findings from CEUS showed hypovascularization of the canine testicular parenchyma caused by the hardening agent. This diagnostic technique helps clinicians define testicular vascular alterations achieved by chemical castration more efficiently. Nevertheless, more studies are required to apply this methodology to more subjects with a broader weight range and stray dogs.